Implementasi Word of Mouth Marketing PT Satu Bintang dalam Mendapat kepercayaan Klien - Rhamadanti, Amanda Aurora; Ardia, Velda (Universitas Garut, 2024)
Abstract This research was conducted to explore the implementation of Word of Mouth marketing implemented by PT Satu Bintang, an event organizer company, in building trust from clients. The purpose of this research is to explain the implementation of PT Satu Bintang's word of mouth marketing in gaining client trust. Employing a qualitative approach with a descriptive methodology, the research systematically portrays phenomena, facts, or events within a specific population or region. Data collection utilizes observation, interviews, and documentation. The findings highlight that PT Satu Bintang utilizes two distinct Word of Mouth marketing implementations, orchestrated by both internal and external entities of the company. Internally, the core team functions as